2020
DOI: 10.2486/indhealth.2020-0073
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative stress induced by occupational exposure to nanomaterials: a systematic review

Abstract: The rapid growth of nanotechnology has increased the occupational exposure to nanomaterials. On the other hand, a growing body of evidence considers exposure to these materials to be hazardous. Therefore, it is necessary to examine the effects of occupational exposure to these materials by different methods. Biological monitoring, especially the investigation of oxidative stress induced by exposure to nanomaterials, can provide useful information for researchers. This study systematically reviews studies that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(7 citation statements)
references
References 44 publications
0
5
0
Order By: Relevance
“…Several studies have searched for the most useful biomarkers of oxidative damage in humans [1][2][3][4][5], and it has been shown that no single marker may be satisfactory [6,7]. The need for nanotoxicology studies in humans is considered vital due to the potential damage to cells, organs, and organisms, and to a lack of human data, especially in occupational settings [8,9], where the exposure is the highest.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have searched for the most useful biomarkers of oxidative damage in humans [1][2][3][4][5], and it has been shown that no single marker may be satisfactory [6,7]. The need for nanotoxicology studies in humans is considered vital due to the potential damage to cells, organs, and organisms, and to a lack of human data, especially in occupational settings [8,9], where the exposure is the highest.…”
Section: Introductionmentioning
confidence: 99%
“…There have been studies stating the potential relationships of oxidative stress biomarkers [ 47 , 48 ] and FENO [ 49 ] with occupational exposure to NMs, but all of them only reviewed the results of known individual articles. No meta-analyses have been conducted to synthesize all data from each study to overcome the low statistical power and achieve a comprehensive and reliable conclusion.…”
Section: Discussionmentioning
confidence: 99%
“…Nowadays, the use of nanomaterials in a various industrial processing, products, and healthcare applications has widely spread 11 , 12 . Due to the lack of a clear toxicological basis for setting nanomaterial-specific occupational exposure limits 13 15 , it is necessary to assess the risk of nanomaterial hazards 16 18 .…”
Section: Introductionmentioning
confidence: 99%